AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA KECAMATAN KESESI KABUPATEN PEKALONGAN (Studi Wilayah Desa Kecamatan Kesesi Kabupaten Pekalongan) Tahun 2015-2016 - Sri Devi Ratnasari, 14.05.52.0184; ardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2018)
This study aims to determine the accountability of village fund allocation management in the Kesesi Subdistrict area of ​​Pekalongan Regency. The management of village fund allocation is examined in three stages, namely the planning, implementation and accountability stages. The study was conducted in 23 villages in the Kesesi Subdistrict, Pekalongan Regency, with a sample of 64 village officials who had authority in managing village finance, especially ADD. The relevant village officials are the village head, secretary, treasurer, and head of affairs. The results showed that village financial management had run well according to Permendagri No. 113 of 2014 and Perbup Pekalongan in 2018. At the planning stage the village government was open to the community and involved the community in planning activities. The implementation phase is carried out by the activity implementing team that the development activities are orderly and in accordance with standards. And the stage of accountability of the village head is responsible for the use of the budget to the regional government, village deliberation bodies, and the community. Keywords: Accountability, Village Fund Allocation, Planning Stage, Implementation Stage, Accountability Stage.